Hand Surgery – Postoperative Recovery and Medical Tourism - Ruxandra Diana Sinescu; Andrea Anghel; Razvan Teohari Vulcanescu (Amfiteatru Economic)
Medical tourism is a growing industry worldwide. Romania has spa treatment facilities that can ensure the development of medical tourism. This article presents a statistical analysis of hand surgery in Romania in 2012. Using adequate quantitative methods we highlight significant differences between age groups and differences regarding procedures that have gender particularities. Recovery after such surgery can be achieved through spa treatment Romania, taking advantage of lower prices compared to other developed countries and numerous medical tourism facilities.